EDUKASI PENANGGULANGAN DAMPAK PEMBELAJARAN DARING TERHADAP KESEHATAN REMAJA SELAMA PANDEMI COVID-19 - Arwan Bin Laeto; Budi Santoso; Siti Sarahdeaz Fazzaura Putri; Syifa Alkaf (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2022)
Health is an important thing that needs to be maintained at all times. The COVID-19 pandemic that has hit the world, including Indonesia, has had a significant impact on the health and social life of teenagers. The social impact experienced by adolescents is in the aspect of education which requires adolescents to take part in online learning. The online learning that teenagers go through has an influence on the health of their bodies. Health complaints experienced by adolescents during online learning include backache, disturbed sleep, eye fatigue and weight gain. Seeing this situation, this community service activity was carried out. This activity involves youth participants and is carried out using educational and demonstration methods. The education provided discussed the impact of online learning during the covid-19 pandemic, the concept of body fitness and forms of exercise in an effort to overcome the impact of online learning. The results obtained indicate that through education, there is an increase in participants' understanding of the various impacts received by adolescents during online learning. In addition, adolescent knowledge related to the concept of fitness and efforts to maintain fitness through exercise has also increased. The sports demonstration provided succeeded in opening the participants' insight that sports can still be done during the covid-19 pandemic, through technology media, both independently and in groups. So it can be concluded that sport is the best effort in overcoming the impact of online learning on adolescent health during the covid-19 pandemic.